Interpretation of Guidance for the Design and Implementation of Drug Clinical Studies: Based on E8 (R1): General Considerations for Clinical Trials - BAI Xiaoyin; YANG Hong (Xiehe Yixue Zazhi, 2023)
As clinical research and drug development in China continue to advance, greater attention has been paid to the value of clinical research guidelines. The first revision of the original E8 recommendations (R1), 'General Considerations for Clinical Research' was made by the International Council for Harmonization in October 2021. Our National Medical Products Administration has recently opted to implement the rules beginning from July 2023. In order to provide useful references for improved design and execution of drug clinical studies in China, this paper primarily interprets the fundamental background and revision of E8 (R1) from the perspective of clinical workers. It also analyzes and discusses the application of the current clinical study guidelines in China.